High-performance Prussian white positive electrode material and preparation method thereof
By covering the iron Prussian blue layer on the surface of the manganese-based Prussian white material, the problem of structural distortion of manganese-based Prussian white positive electrode material during the cycle is solved, and the stability and electrochemical properties of the material are significantly improved, which is suitable for industrial production. Reduced costs.
Patent Information
- Application Number
- CN202411449550.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-10
AI Technical Summary
Manganese-based Prussian white positive electrode material is prone to manganese ion dissolution and structural distortion during the circulation process, resulting in capacity decay, limiting its practical application.
The iron-based Prussian blue layer is coated on the surface of manganese-based Prussian white material by acid etching and ion exchange to form a core-shell structure. The high-performance Prussian white positive electrode material is prepared through acid etching and ion exchange methods to enhance the structural stability and electrical properties of the material. Chemical properties.
It significantly improves the structural stability and electrochemical properties of the material, enhances the rate performance and long cycle performance, reduces production costs, and is suitable for large-scale industrial production.
Smart Images

Figure CN119297242A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion battery electrode materials, and in particular to a high-performance Prussian white positive electrode material and a preparation method thereof. Background Art
[0002] In the face of increasingly severe energy challenges, it is particularly important to find efficient energy storage solutions. Lithium-ion batteries have been widely used in the field of power energy storage due to their superior energy density and long-term stability. However, the scarcity and rising costs of lithium resources limit their sustainable development. Therefore, sodium-ion batteries, as an emerging energy storage technology, have gradually attracted attention due to their abundant raw materials, low cost, and similar operating mechanism to lithium-ion batteries. Sodium-ion batteries are considered to be a strong competitor in the future energy storage field.
[0003] Among the cathode materials of sodium-ion batteries, Prussian blue analogs have shown significant advantages in energy storage due to their unique framework structure. In particular, manganese-based Prussian white cathode materials have a high specific capacity. However, due to the Jan-Taylor effect of manganese ions, this material is prone to manganese ion dissolution and structural distortion during the cycle, resulting in severe capacity decay, which limits its practical application. In contrast, iron-based Prussian blue cathode materials have obvious advantages in conductivity and cycle stability. Iron-based Prussian blue is relatively stable during the cycle, and is not prone to phase change and structural collapse. Its performance is better than other Prussian blue cathode materials. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the manganese-based Prussian white positive electrode material in the prior art in terms of structural stability.
[0005] To achieve the above-mentioned purpose, the present invention proposes a high-performance Prussian white positive electrode material, which has a core-shell structure, has high stability, and exhibits excellent rate performance and cycle performance; the positive electrode material includes a manganese-based Prussian white material core and an iron-based Prussian blue coating layer arranged on the surface of the manganese-based Prussian white material core, and the positive electrode material is prepared by acid etching and ion exchange methods.
[0006] The present invention also provides a method for preparing a high-performance Prussian white positive electrode material. The method for preparing the high-performance Prussian white positive electrode material comprises the following steps:
[0007] S1: dispersing unmodified Prussian white positive electrode material and sodium ferrocyanide in deionized water in proportion to obtain a manganese-based Prussian white material mixed solution;
[0008] S2: adding an acid substance to the mixed solution of the manganese-based Prussian white positive electrode material, and forming an iron-based Prussian blue coating layer on the surface of the manganese-based Prussian white positive electrode material through ion exchange to obtain a solid material;
[0009] S3: separating and treating the solid material;
[0010] S4: After drying the separated solid material, an iron-based Prussian blue-coated Prussian white positive electrode material is obtained.
[0011] Furthermore, in step S1, the reaction temperature is maintained at 25-90°C.
[0012] Further, in step S1, the unmodified Prussian white positive electrode material is Na x Mn[Fe(CN)6] y , 0 <x≤2,0<y≤1。
[0013] Furthermore, in step S1, the mass ratio of the unmodified Prussian white positive electrode material to sodium ferrocyanide is 1:1-1:0.5.
[0014] Furthermore, the unmodified Prussian white positive electrode material is in the form of solid powder.
[0015] Furthermore, in step S2, the acid substance is any one of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid or acetic acid.
[0016] Furthermore, in step S3, the separation treatment method is centrifugal washing, and the washing solvent of the centrifugal washing is deionized water or anhydrous ethanol.
[0017] Furthermore, in step S4, the drying treatment method is air drying or vacuum drying; the drying temperature is 80-150° C., and the drying time is 12-24 hours.
[0018] Furthermore, the prepared high-performance Prussian white positive electrode material is applied to sodium ion battery electrode materials.
[0019] Compared with the prior art, the advantages of the present invention are:
[0020] 1. The present invention adopts acid etching and ion exchange methods to prepare high-performance manganese-based Prussian white positive electrode materials. By uniformly coating the surface of manganese-based Prussian white particles with iron-based Prussian blue, it not only effectively inhibits the metal ion dissolution and structural distortion problems caused by the Jan-Taylor effect, significantly improves the structural stability of the material, but also enhances the overall electronic conductivity and ion diffusion rate of the positive electrode material, so that the electrochemical performance of the prepared positive electrode material is further improved, thereby showing better rate performance and long cycle performance.
[0021] 2. The present invention uses cheap Prussian blue as raw material, which effectively reduces production costs.
[0022] 3. The method of the present invention has simple process, environmental protection, high yield, low equipment requirements, easy operation, good controllability, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is an X-ray diffraction spectrum of the MnHCF@FeHCF-1 material synthesized in Example 1 of the present invention;
[0024] Figure 2 This is a scanning electron microscope photograph of the MnHCF@FeHCF-1 particles synthesized in Example 1 of the present invention;
[0025] Figure 3 The cycle performance diagram of the MnHCF@FeHCF-1 synthesized in Example 1 of the present invention and the unmodified MnHCF electrode material;
[0026] Figure 4 This is a rate performance diagram of the MnHCF@FeHCF-1 synthesized in Example 1 of the present invention and the unmodified MnHCF electrode material;
[0027] Figure 5 This is a scanning electron microscope photograph of the MnHCF@FeHCF-2 particles synthesized in Example 2 of the present invention;
[0028] Figure 6 The cycle performance diagram of the MnHCF@FeHCF-2 synthesized in Example 2 of the present invention and the unmodified MnHCF electrode material;
[0029] Figure 7 This is a transmission electron microscope photo of the MnHCF@FeHCF-3 particles synthesized in Example 3 of the present invention;
[0030] Figure 8 This is a rate performance diagram of the MnHCF@FeHCF-3 synthesized in Example 3 of the present invention and the unmodified MnHCF electrode material. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be further described below.
[0032] Comparative Example
[0033] The unmodified pure MnHCF material was used as a comparative example.
[0034] Example 1
[0035] This embodiment 1 proposes an iron-based Prussian blue-coated manganese-based Prussian white positive electrode material, and the specific preparation method thereof is as follows:
[0036] S1.1: Dissolve 500 mg of MnHCF and 500 mg of Na4Fe(CN)6·10H2O in 100 mL of deionized water and treat by ultrasonic for 30 min to obtain a mixed solution;
[0037] S1.2: Heat the obtained mixed solution to 90℃, add 5mL of HNO3 (concentration 1mol / L) under stirring, and continue stirring for 4h. Under the action of acid, [Fe(CN)6] 4- Partial decomposition to form a FeHCF coating;
[0038] S1.3: Wash by centrifugation with deionized water and anhydrous ethanol for 3 times to achieve separation;
[0039] S1.4: The solid material obtained after separation is placed in a vacuum oven at 150°C and dried for 12 hours to obtain MnHCF with a uniform surface FeHCF coating, which is recorded as MnHCF@FeHCF-1 composite material.
[0040] The X-ray diffraction spectrum of the MnHCF@FeHCF-1 composite material of Example 1 is as follows: Figure 2 As shown, from Figure 2 It can be seen that the XRD pattern of the synthesized product MnHCF@FeHCF-1 composite material is a typical cubic structure, which indicates that the crystal structure is not changed after coating the FeHCF layer; in addition, by amplifying the characteristic peaks (220) and (400), it can be found that the XRD pattern of the MnHCF@FeHCF-1 composite material of Example 1 is superimposed by MnHCF and FeHCF, indicating that these two substances exist in the composite material and FeHCF is successfully coated on the surface of MnHCF. At the same time, the scanning electron microscope photo of MnHCF@FeHCF-1 of Example 1 is shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the FeHCF film coated on the surface is uniform and complete.
[0041] The MnHCF@FeHCF-1 composite material of Example 1 was assembled into a half-cell, and its electrochemical performance was tested. The specific assembly test method is as follows:
[0042] 1) Mix the material with 20wt% of a binder and 10wt% of a conductive agent, stir evenly, coat the mixture on an aluminum foil, and place the mixture in an oven to dry at 60-80°C, wherein the binder is a 4wt% N-methylpyrrolidone solution of polyvinylidene fluoride, and the conductive agent is Super P;
[0043] 2) Punch out the electrode piece with a punch having a diameter of 10 mm, put it into a vacuum oven and dry it at 60-120° C. for 12-24 h, and then transfer it to a glove box filled with argon.
[0044] 3) A CR2032 button cell was assembled using a sodium metal sheet as a counter electrode, a glass fiber membrane as a separator, a 1 mol / L NaClO4 EC / DMC (volume ratio 1:1) mixed solution as an electrolyte, and 1% vol FEC as an electrolyte additive;
[0045] 4) The assembled CR2032 button cell was tested for constant current charge and discharge performance on the LAND battery test system (provided by Wuhan Jinnuo Electronics Co., Ltd.), where the charge and discharge cut-off voltage was relative to Na / Na + 2-4V.
[0046] The pure MnHCF material of the comparative example was assembled and tested according to the test method in Example 1, and the constant current charge and discharge performance test was also carried out. The test results of the two are as follows: Figure 3 and Figure 4 As shown, Figure 3 The cycling performance comparison of pure MnHCF material and MnHCF@FeHCF-1 composite material at 1C rate is shown in Figure 2. Figure 3 It can be seen that the charge and discharge capacity of the MnHCF@FeHCF-1 composite material of Example 1 reaches 103 mAh / g under the condition of 1C current (charge and discharge time is 1 h each), and the capacity retention rate is still close to 80.1% after 500 cycles, while the capacity retention rate of the unmodified pure MnHCF material in Comparative Example 1 is only 30.8% after 500 cycles, indicating that the MnHCF@FeHCF-1 composite material of Example 1 exhibits more excellent long cycle performance; Figure 4 The rate performance comparison diagram of the pure MnHCF material of the comparative example and the MnHCF@FeHCF-1 composite material of Example 1 is shown in FIG. Figure 4 It can be seen that even under the condition of a high current of 10C, the MnHCF@FeHCF-1 composite material of Example 1 still has a higher specific capacity than the pure MnHCF material of the comparative example.
[0047] Example 2
[0048] This embodiment 2 proposes an iron-based Prussian blue-coated manganese-based Prussian white positive electrode material, and the specific preparation method thereof is as follows:
[0049] S2.1: Dissolve 500 mg of MnHCF and 400 mg of Na4Fe(CN)6·10H2O in 100 mL of deionized water and treat by ultrasonic for 30 min to obtain a mixed solution;
[0050] S2.2: Heat the obtained mixed solution to 60°C, add 5 mL of HCl (concentration 1 mol / L) under stirring, and continue stirring for 4 h. Under the action of acid, [Fe(CN)6] 4- Partial decomposition to form a FeHCF coating;
[0051] S2.3: Wash by centrifugation with deionized water and anhydrous ethanol for 3 times to achieve separation;
[0052] S2.4: The solid material obtained after separation is placed in a vacuum oven at 120°C and dried for 12 hours to obtain MnHCF with a uniform surface FeHCF coating, which is recorded as MnHCF@FeHCF-2 composite material.
[0053] The scanning electron microscope photo of the MnHCF@FeHCF-2 composite material of Example 2 is shown in FIG. Figure 5 As shown, from Figure 5 It can be seen that the surface of the MnHCF@FeHCF-2 composite becomes rough while maintaining the cubic microstructure, but is still coated with a very uniform FeHCF coating, indicating complete coverage of the FeHCF layer.
[0054] The MnHCF@FeHCF-2 composite material of Example 2 was assembled into a half-cell according to the assembly test method in Example 1 and subjected to a constant current charge and discharge performance test on a LAND battery test system (provided by Wuhan Jinnuo Electronics Co., Ltd.). The cycle performance test results at a 1C rate were compared with the test results of the pure MnHCF material of the comparative example. Figure 6 As shown, from Figure 6 It can be seen that the charge and discharge capacity of the MnHCF@FeHCF-2 composite material of Example 2 reaches 95.2 mAh / g under 1C current conditions (charge and discharge time is 1 h each), and the capacity retention rate is still close to 62.7% after 500 cycles, which is much higher than the unmodified pure MnHCF material in the comparative example.
[0055] Example 3
[0056] Example 3 proposes an iron-based Prussian blue-coated manganese-based Prussian white positive electrode material, and the specific preparation method thereof is as follows:
[0057] S2.1: Dissolve 500 mg of MnHCF and 250 mg of Na4Fe(CN)6·10H2O in 100 mL of deionized water and treat by ultrasonic for 30 min to obtain a mixed solution;
[0058] S2.2: During the stirring process, add 5 mL of H2SO4 (concentration 1 mol / L) to the mixture and continue stirring for 4 h. Under the action of the acid, [Fe(CN)6] 4-Partial decomposition to form a FeHCF coating;
[0059] S2.3: Wash by centrifugation with deionized water and anhydrous ethanol for 3 times to achieve separation;
[0060] S2.4: The solid material obtained after separation is placed in a vacuum oven at 100°C and dried for 12 hours to obtain MnHCF with a uniform surface FeHCF coating, which is recorded as MnHCF@FeHCF-3 composite material.
[0061] The transmission electron microscopy image of the MnHCF@FeHCF-3 composite material is shown in Figure 7 As shown, from Figure 7 It can be seen that the MnHCF@FeHCF-3 composite material of Example 3 has a rough edge and an obvious coating with a thickness of about 10-35 nm, and the FeHCF coating hardly changes the morphology of the MnHCF@FeHCF-3 particles, which still have a cubic structure.
[0062] The MnHCF@FeHCF-3 composite material of Example 3 was assembled into a half-cell according to the assembly test method in Example 1 and subjected to constant current charge and discharge performance test on a LAND battery test system (provided by Wuhan Jinnuo Electronics Co., Ltd.). The charge and discharge cut-off voltage was relative to Na / Na + The rate performance test results of the MnHCF@FeHCF-3 composite material are compared with those of the pure MnHCF material in the comparative example. Figure 8 As shown, from Figure 8 It can be seen that after 10C charge and discharge, the capacity of the MnHCF@FeHCF-3 composite material of Example 3 remains at 70.6 mAh / g, which is still higher than that of the comparative example, showing good rate performance.
[0063] It can be seen from the above embodiments that the present invention prepares a high-performance iron-based Prussian blue-coated manganese-based Prussian white composite positive electrode material by acid etching and ion exchange, which can effectively inhibit the Jan-Taylor effect, reduce the dissolution of metal ions and the occurrence of side reactions, and significantly improve the structural stability of the material during the charge and discharge process. In addition, the presence of the iron-based Prussian blue coating layer enhances the electronic conductivity and ionic conductivity of the material, significantly improves the electrochemical performance, and exhibits better rate performance and long cycle performance.
[0064] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any technician in the relevant technical field, without departing from the scope of the technical solution of the present invention, makes any form of equivalent replacement or modification to the technical solution and technical content disclosed in the present invention, which does not depart from the content of the technical solution of the present invention and still falls within the protection scope of the present invention.
Claims
1. A high-performance Prussian white cathode material, characterized in that: The positive electrode material is a core-shell structure, and the positive electrode material comprises a manganese-based Prussian white material core and an iron-based Prussian blue coating layer arranged on the surface of the manganese-based Prussian white material core.
2. A method for preparing a high-performance Prussian white positive electrode material, comprising preparing the high-performance Prussian white positive electrode material as claimed in claim 1, characterized in that: The steps include: S1: dispersing unmodified Prussian white positive electrode material and sodium ferrocyanide in deionized water in proportion to obtain a manganese-based Prussian white material mixed solution; S2: adding an acid substance to the mixed solution of the manganese-based Prussian white positive electrode material, and forming an iron-based Prussian blue coating layer on the surface of the manganese-based Prussian white positive electrode material through ion exchange to obtain a solid material; S3: separating and treating the solid material; S4: After drying the separated solid material, an iron-based Prussian blue-coated Prussian white positive electrode material is obtained.
3. The method for preparing a high-performance Prussian white positive electrode material according to claim 2, characterized in that: In step S1, the reaction temperature is maintained at 25-90°C.
4. The method for preparing a high-performance Prussian white cathode material according to claim 2, characterized in that: In step S1, the unmodified Prussian white positive electrode material is Na x Mn[Fe(CN)6] y , 0 <x≤2,0<y≤1。 5. The method for preparing a high-performance Prussian white cathode material according to claim 2, characterized in that: In step S1, the mass ratio of the unmodified Prussian white positive electrode material to sodium ferrocyanide is 1:1-1:0.
5.
6. The method for preparing a high-performance Prussian white cathode material according to claim 2, characterized in that: In step S1, the unmodified Prussian white positive electrode material is in the form of solid powder.
7. The method for preparing a high-performance Prussian white cathode material according to claim 2, characterized in that: In step S2, the acid substance is any one of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid or acetic acid.
8. The method for preparing a high-performance Prussian white cathode material according to claim 2, characterized in that: In step S3, the separation treatment method is centrifugal washing, and the washing solvent of the centrifugal washing is deionized water or anhydrous ethanol.
9. The method for preparing a high-performance Prussian white cathode material according to claim 2, characterized in that: In step S4, the drying treatment method is air drying or vacuum drying; the drying temperature is 80-150° C., and the drying time is 12-24 hours.
10. The method for preparing a high-performance Prussian white cathode material according to claim 2, characterized in that: The prepared high-performance Prussian white positive electrode material is applied to sodium ion battery electrode materials.
Citation Information
Cited By
Modified sodium ion battery positive electrode material and preparation method and application thereof
CN119612553A
Positive electrode material and preparation method and application thereof
CN119905558A